Assessing safety culture and safety performance in a high hazard industry - Jones, Ceri (2014)
In the UK 27 million working days are lost due to work-related illness or injury; at an estimate of £13.4 billion to the economy. Over the last 30 years researchers have examined safety culture and its relationship to poor safety performance. An organisation in the high hazard construction industry wanted to understand the factors that shaped and influenced safety performance and safety culture. This thesis details a research project which addresses that aim. A multi-method, triangulated approach was adopted combining both qualitative (focus groups and interviews) and quantitative (safety climate questionnaire) methods. The results of the qualitative studies informed the development of the safety climate questionnaire that included a measure of self-reported accidents and near misses.